Age-Related Changes in the Histoarchitecture of Ovary in Domestic Short Hair Cat - Bhargavi, S. (Indian Journal of Veterinary Anatomy, 2020)
admitted for elective ovario-hysterectomy at Madras Veterinary College Teaching Hospital. The tissue samples were fixed in 10% neutral buffered formalin and processed for paraffin sectioning. 3-5μm sections were cut and stained by write names of stains. The tunica albuginea was made of dense irregular connective tissue and was lined externally by a layer of low cuboidal or simple squamous epithelium. The parenchyma was made up of an outer cortex and inner medulla. Cortex consisted of primordial, primary, secondary, pre-antral and antralfollicles. The number of primordial follicles was more in juvenile cat when compared to adult. Primary follicles were lined by simple cuboidal epithelium. The thecal layer beneath the basement membrane differentiated into theca interna and theca externa.